Evaluación in vitro del efecto antibacteriano de cinco propóleos peruanos sobre cepas de Streptococcus mutans (ATCC 25175) y Streptococcus sanguinis (ATCC 10556) - Jara Muñoz, Rocío del Pilar (2014)
The target was evaluate the “in vitro” antibacterial effect about five peruvian propolis on strains of Streptococcus mutans (ATCC 25175) and Streptococcus sanguinis (ATCC 10556), Having an experimental study design “in vitro” made in laboratorie of Microbiology of the Peruvian University of Applied Sciences. Materials and Methods: Sample size were about ten holes for each of the five extracts of propolis, either for Streptococcus mutans and Streptococcus sanguinis individualy. The antibacterial effect was developed with the technical “Agar overlay interference test”, which is used 200ml of Agar BHI homogenized with bacteria indispensably (a bottle for bacteria). This agar is distributed in the plates, once solidified the holes are made with 150μL of different kinds of propolis and the control group called Clorhexidine 0.12%. Completed this process is placed in the anaerobiosis chamber on 37º C, for 72 hours. Finally, the measurement of the inhibitory halo is made. Results: The methanolic extract of propolis of Oxapampa-Perú present inhibition halos in larger averaging of 33.15 + 3.26 mm against strains of Streptococcus mutans (ATCC 25175) and Streptococcus sanguinis (ATCC 10556), their average was about 23.23 + 0.82mm. In case of 4 extracts of commercial, just 3 of them (tincture of propolis Farmagel, Madre Nature y Kaita®), had bacterian activity in front of the studies strains. In all cases the antibacterian activity is less than positive control. Conclusions: The methanolic extract of propolis of Oxapampa-Peru, made in the laboratory has better antibacterian activity than commercial extracts against strains of Streptococcus mutans (ATTC 25175) and Streptococcus sanguinis (ATCC 10556). About the four commercial propolis evaluated on this study, propolis tincture Farmagel, Kaita®, Madre Natura and Max propolis tincture, only three of this have antibacterial activity against strains of de Streptococcus mutants (ATCC 25175) and Streptococcus sanguinis (ATCC 10556).